2017
DOI: 10.1016/j.ihj.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-angiographic profile and procedural outcomes in patients undergoing percutaneous coronary interventions: The Srinagar registry

Abstract: BackgroundThis study was aimed at exploring the clinical profile, angiographic characteristics and procedural outcomes in patients undergoing PCI at our institute.MethodsThis prospective observational study included all consecutive patients who underwent PCI at our hospital between January 2014 and December 2015. Data including clinico-demographic profile, angiographic details and lesion characteristics were recorded in all patients. Procedural details including devices and drugs used, procedure related compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
(35 reference statements)
5
15
1
7
Order By: Relevance
“…According to the INTERHEART study [8], the median age for the presentation of CAD in the South Asian population is 53 years which was consistent with our study but earlier than the western population as feature in COURAGE trial (62 years) [9]. In contrary to the Beig et al study [10], CAD was presented earlier in female (mean age 50.25 ± 11.44) compared to men (mean age 55.00 ± 9.46) in our study. Sex ratio observed was 3.25:1 (76.47% male) and this can be attributed to the gender bias which is also a similar feature in INTERHEART study (75.9% male) [11].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…According to the INTERHEART study [8], the median age for the presentation of CAD in the South Asian population is 53 years which was consistent with our study but earlier than the western population as feature in COURAGE trial (62 years) [9]. In contrary to the Beig et al study [10], CAD was presented earlier in female (mean age 50.25 ± 11.44) compared to men (mean age 55.00 ± 9.46) in our study. Sex ratio observed was 3.25:1 (76.47% male) and this can be attributed to the gender bias which is also a similar feature in INTERHEART study (75.9% male) [11].…”
Section: Discussionsupporting
confidence: 88%
“…The clinical presentations showed 29.41% patients presented with chronic stable angina and together the acute coronary syndrome constituted 70.59% was the most common presentation included UA, STEMI, and USTEMI similar to Sharma et al study [2]. SVD was the most common angiographic pattern, followed by DVD and TVD observed in Beig et al [10] and Sharma et al study [2]. Where in our study, SVD of LMCA was most common pattern observed in 47.10% patients followed by TVD (29.41%) and DVD (23.53%).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, these findings of Bassan et al are contradicted by Thrombolysis in Acute Myocardial Infarction (TAMI) [12] and Thrombolysis in Myocardial Infarction (TIMI) [13] populations. Many studies have proven that the LAD is the most common coronary artery involved by atherosclerosis, especially type V atherosclerosis and in myocardial infarction [14][15][16]. Our study showed that 12.0%, 11.2% and 7.7% of patients had significant LAD, RCA and LCX obstruction, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…2019 Oct;7 (10): [3819][3820][3821][3822][3823][3824] International Journal of Research in Medical Sciences | October 2019 | Vol 7 | Issue 10 Page 3820 complex patients and lesions being treated with this modality. 5 Despite, this increasing panorama, ISR is the major limitation impeding the medium-term efficacy of coronary stenting. 6,7 Sirolimus-eluting (SES) and paclitaxeleluting stents (PES), the two drug-eluting stents (DES) most extensively studied so far have markedly altered the outcome of patients undergoing coronary angioplasty, mainly due to their effect on the reduction of restenosis.…”
Section: Introductionmentioning
confidence: 99%